Uncovering the Reflections of English Medium Instruction in Engineering Graduates’ Career - Mehmet Altay; Nalan Erçin (Sakarya University Journal of Education)
English Medium Instruction (EMI) is increasingly recognized as an intriguing phenomenon for researchers in not only Higher Education (HE) but also professional context. Although engineering is one of the most appealing field in this regard, little has been done to investigate the influence of EMI over graduates’ career. Two types of EMI, partial and full, applied in Turkey were compared in this current study to determine the market type addressed by the organizations for which engineering graduates work (n=76). A second purpose with this comparison was to make inferences from their reflections over the role of English for learning in their being employed. Findings showed that being a full or partial EMI graduate do not indicate a significant difference in the type of market addressed as well as in being employed. The last aim of the study was to identify the types of proficiency tests in English the graduates of different engineering subjects were required to take, if any. It was seen that there is a significant difference in the testing procedure depending on the subjects.